MENINGKATKAN KOMPETENSI BERBICARA MAHASISWA DENGAN PENDEKATAN PEMBELAJARAN TERINTEGRASI - Isli Iriani Indiah Pane (BAHAS, 2009)
The objective of this research is aimed to find out how the process of integrated learning approach can improve students’ speaking competences, especially  in descriptive genre. The action research was undertaken at 2008 class A, English Education department students. There were 29 students of 2008 class A, English Education department students involved in the research. The data were taken  by applying integrated learning approach in teaching Speaking I course and taking filed notes, conversation record, test, and students’ worksheet. The findings indicate that (1) integrated learning approach can improve the students’ speaking competences  significantly when it is given simultanously by grammatical aspects. (2) by giving the well designed worksheet can lead the students to achieve the speaking competences needed easily (3) the mastery of vocabulary competences is one of the main requirements in writing descriptive paragraph. (4) in writing descriptive paragraph, the students should arrange the information given from the general to the specific ones. Keywords: Integrated learning approach, speaking competences, descriptive genre